COVID-19 Lockdown Restrictions and Online Media Consumption in Germany - Lemenager, Tagrid; Neissner, Miriam; Koopmann, Anne; Reinhard, Iris; Georgiadou, Ekaterini; Müller, Astrid; Kiefer, Falk; Hillemacher, Thomas (International journal of environmental research and public health, 2020)
The lockdown restrictions due to the COVID-19 pandemic have led to increased stress levels and feelings of anxiety in the general population. Problematic usage of certain online applications is one frequent way to compensate for negative feelings and stress. The current study investigated changes of online media consumption during the lockdown in Germany. Gender and age specific differences in specific online activities were assessed. n = 3245 subjects participated in an online survey conducted between the 8th April and the 11th May 2020. Participants’ age ranged between 18 and >55 years. A considerably high percentage (71.4%) of participants reported increased online media consumption during the lockdown. Male participants were more likely to increase their consumption of gaming and erotic platforms, while female participants reported a higher increase in the engagement in social networks, information research, and video streaming than males. The findings revealed an increased usage of all online applications during the lockdown. For the clarification whether the increase might present a risk for elevated Internet-use disorders or can be regarded as a functional and time-limited phenomenon, further studies, assessing changes in these online activities after the end of the pandemic, are needed.